Sedimentary patterns and exploitation practices of tight-sand gas reservoirs in coal measure strata: A case study of the 3rd submember of the second member of the Permian Shanxi Formation in the Daning-Jixian block - Lei ZHANG; Li HUANG; Longmei ZHAO; Feng WANG; Yixin ZHANG; Shi SHI; Wen ZHANG; Haoyang ZHAO; Tong CHEN; Jiangnan TONG (Meitian dizhi yu kantan)
BackgroundThe third submember of the second member of the Permian Shanxi Formation (also referred to as the Shan 23 submember) in the Daning-Jixian block along the eastern margin of the Ordos Basin is identified as a primary target layer for tight-sand gas production in the block. In the early stage of the block development, play fairways were initially identified through fundamental studies on provenance areas and sedimentary systems. Accordingly, a gas field with an annual production of 10 × 108 m3 was constructed in the block. However, further exploitation reveals that the sandstones in the Shan 23 submember exhibit a reduced thickness, a decreased scale, and significant differences in the characteristics of sand bodies along different directions of provenance areas. Existing findings are insufficient to effectively guide research on sand body distribution and well placement. This severely constrains subsequent exploitation. MethodsUsing data from outcrop and core observations, logs, 3D seismic surveys, analyses, and assays of the Daning-Jixian block, this study established a high-resolution sequence stratigraphic framework for the Shan 23 submember. Furthermore, this study conducted a fine-scale investigation of sedimentary microfacies in the Shan 23 submember and determined the origin and distribution of the bottom sandstones in this submember. ResultsThe results indicate that the Shan 23 submember is a part of an incomplete symmetrical cycle dominated by rising semicycles, with bottom sandstones occurring primarily in the lower short-term cycles. The sedimentary system in the Shan 23 submember exhibits a large-scale braided river delta sedimentary system in the north and a relatively small-scale meandering river delta sedimentary system in the south. Moreover, the bottom sandstones in the north and south manifest significantly different delta-front distributary channel microfacies. The paleogeomorphic reconstruction suggests that the distribution of the bottom sandstones in the Shan 23 submember is governed by the paleo-trench in the underlying Taiyuan Formation. This study established a sedimentary pattern indicating that the sand body scale is controlled by both dual provenance areas and accommodation space and that the sandstone enrichment areas are subjected to both paleogeomorphology and sedimentary microfacies. Accordingly, this study identified a sedimentary framework consisting of five primary subaqueous distributary channels in the block. Differentiated well placement was conducted based on the channel distribution characteristics, with horizontal wells deployed in the north and vertical cluster wells in the south. This well placement strategy contributed to remarkable results, significantly enhancing the probability of penetration for sandstones and the gas production of both horizontal wells and vertical cluster wells. Specifically, for the horizontal wells, the probability of penetration and average production increased by 15% and 66.7%, respectively, with a maximum daily production reaching up to 20 × 104 m3; for the vertical cluster wells, the probability of penetration and average production increased by 11% and 45.4%, respectively, with a maximum daily production reaching up to 5 × 104 m3. ConclusionsThe accurate prediction of the distribution pattern of channel sand bodies with a control mode of dual provenance areas provides significant support for the efficient exploitation of the Shan 23 submember in the Daning-Jixian block while also offering a reference for the production of tight-sand gas under similar geological conditions along the eastern margin of the Ordos Basin.